Perlindungan Hukum terhadap Pemilik Tanah Atas Pemasangan Jaringan Listrik oleh PT.PLN (Persero) - Khoiruni Azzahra, Kamila; Suhermi, Suhermi; Windarto, Windarto (Zaaken: Journal of Civil and Business Law, 2024)
This study aims to determine and analyze the form of legal protection of landowners for the installation of electricity network facilities and to find out the settlement efforts against owners whose rights are not protected due to the installation of electricity networks by PT PLN (Persero. The formulation of the problem in this study is how the legal protection of landowners for the installation of electricity networks by PT PLN (Persero) and how the settlement efforts against landowners whose rights are not protected due to the installation of electricity networks by PT PLN (Persero). The research method used is the juridical-empirical method, namely making observations of legal facts that apply. The result of this study is that landowners have not received legal protection for the installation of electricity networks by PT. PLN (Persero). For this reason, the effort made by the landowner is to submit the removal of the pole to PT. PLN (Persero) is charged.